2014
DOI: 10.1007/s00345-014-1269-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3 T pelvic MRI imaging in prostate cancer patients receiving post-prostatectomy IMRT

Abstract: Post-prostatectomy patients with pathologic positive margins are three times more likely to have positive findings on a 3 T MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Patients who benefited most from undergoing an MRI were those with PSADT longer than 14 months or with pre-SRT PSA greater than 0.5 ng/ml. While in other studies the correlation between the incidence of rLR and the PSA value or positive surgical margins at RP has already been proven [15,19,20] to the authors' knowledge, this is the first study to research and find a significant relationship between the PSADT and the rLR through MRI. This correlation between the PSA value and the PSADT value with rLR may help in the selection of those patients who will benefit most from MRI.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Patients who benefited most from undergoing an MRI were those with PSADT longer than 14 months or with pre-SRT PSA greater than 0.5 ng/ml. While in other studies the correlation between the incidence of rLR and the PSA value or positive surgical margins at RP has already been proven [15,19,20] to the authors' knowledge, this is the first study to research and find a significant relationship between the PSADT and the rLR through MRI. This correlation between the PSA value and the PSADT value with rLR may help in the selection of those patients who will benefit most from MRI.…”
Section: Discussionmentioning
confidence: 84%
“…Two articles [15,19] found, as did the present work, a 22-24% incidence of rLR through MRI, with a median PSA of 0.5 ng/ml or lower. However, in two other studies, the incidence of rLR was surprisingly high, at 67% and 91%, respectively [20,21]. The exact reason for this discrepancy is not known, and it may be due to the influence of several factors, such as the small sample size of the studies, their retrospective nature, the various clinical features of the patients, MRI sequences and protocols, MRI antenna and magnet, the experience of the radiologists or the standard reference used for each study.…”
Section: Discussionmentioning
confidence: 91%
“…They found that 20% of these patients had positive MRI findings, of whom 80% had PSA values <1ng/mL. Positive surgical margins at RP was a predictor of positive MRI findings [14]. Wassberg et al analyzed 51 patients with suspicious T2W MRI findings and 33 (63%) of the biopsies were positive for recurrent prostate cancer [15].…”
Section: 0 Discussionmentioning
confidence: 99%
“…The treatment was changed in 7 of 18 patients due to the MRI findings; these changes consisted of an extra boost up to 77.4 Gy to the detected lesion on MRI or pelvic lymph nodes that were also irradiated. So, it seems that in case of a PSM a MRI can aid with the localization of the target volume for salvage treatment in some patients [113], but it is still unclear if this approach will influence outcome. Müller et al verified the positive findings on mpMRI with ultrasound-registered biopsies.…”
Section: Role Of Mri Following Radical Prostatectomy To Identify Locomentioning
confidence: 99%
“…In a pooled analysis by Yu et al, the pooled sensitivity and specificity for dynamic contrast-enhanced MRI in detecting residual or recurrent disease following prostatectomy was 0.88 and 0.87, respectively, in the 12 studies reviewed [115]. In most studies, patients with positive MRI findings had higher PSA levels [113]. Dirix et al found a PSA level of 1.4 ng/ml in the patients with positive findings on MRI compared to 0.4 ng/ml in the negative group [116].…”
Section: Role Of Mri Following Radical Prostatectomy To Identify Locomentioning
confidence: 99%